2021
DOI: 10.18632/aging.203245
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the prognosis and immune infiltration for CXC chemokines in colorectal cancer

Abstract: The C-X-C motif (CXC) chemokines are a family of chemotactic molecules that have been identified as potential prognostic markers and prospective therapeutic targets for many kinds of cancer types. Increasing evidence shows that CXC chemokines are associated with the progression of colorectal cancer (CRC); however, the correlations of CXC chemokines with prognostic and immune infiltrates in CRC remain to be clarified. In this study, we analyzed the mRNA expression level, prognostic data and immune infiltrates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
10
12
0
Order By: Relevance
“…Patients with COAD also showed downregulated CXCL12/13/14 expression. The results were similar to those reported in a previous study in patients with COAD [ 30 ] and contradicted those reported previously in patients with colorectal cancer [ 29 ]. This may be due to the small sample size and the variable types of colorectal cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Patients with COAD also showed downregulated CXCL12/13/14 expression. The results were similar to those reported in a previous study in patients with COAD [ 30 ] and contradicted those reported previously in patients with colorectal cancer [ 29 ]. This may be due to the small sample size and the variable types of colorectal cancer.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, studies have identified VEGFA and CXC chemokines as important participants in angiogenesis, particularly tumor angiogenesis [14,15,[26][27][28]. The expression levels of CXC chemokines and VEGFA have been studied in a range of tumor types; however, findings are contradictory with regard to colonic adenocarcinomas [29,30]. This study investigated expression level, gene regulatory network, prognostic value, and target prediction of the CXC chemokine-VEGFA network for COAD from a tumor angiogenesis perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COAD also showed downregulated CXCL12/13/14 expression. The results were same with those in a previous study in patients with COAD 25 , and contradict previous ndings in patients with colorectal cancer 24 . This may be due to the small sample size and the many different types of colorectal cancer.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, studies have identi ed VEGFA and CXC chemokines as important participants in angiogenesis, particularly tumor angiogenesis 12,22,23 . The expression levels of CXC chemokines and VEGFA have been studied in a range of tumor types; however, ndings are contradictory with regard to colonic adenocarcinomas 24,25 . This study investigated expression level, gene regulatory network, prognostic value, and target prediction of the CXC chemokine-VEGFA network for COAD from the perspective of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Prior studies found increased chemokine expression in tissues from colorectal cancer patients was associated with disease progression [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%